Diastereo‐ and Enantioselective Hydrophosphination of Cyclopropenes under Lanthanocene Catalysis - Lin, Xiaobin; An, Kun; Zhuo, Qingde; Nishiura, Masayoshi; Cong, Xuefeng; Hou, Zhaomin (Angewandte Chemie International Edition, 2023)
The asymmetric hydrophosphination of cyclopropenes with phosphines is of much interest and importance, but has remained hardly explored to date probably because of the lack of suitable catalysts. We report here the diastereo‐ and enantioselective hydrophosphination of 3,3‐disubstituted cyclopropenes with phosphines by a chiral lanthanocene catalyst bearing the C2‐symmetric 5,6‐dioxy‐4,7‐trans‐dialkyl‐substituted tetrahydroindenyl ligands. This protocol offers a selective and efficient route for the synthesis of a new family of chiral phosphinocyclopropane derivatives, featuring 100 % atom efficiency, good diastereo‐ and enantioselectivity, broad substrate scope, and no need for a directing group. A chiral lanthanocene complex served as a unique catalyst for the asymmetric hydrophosphination of cyclopropenes with phosphines, efficiently affording a new family of chiral phosphinocyclopropane derivatives in high yields with good diastereo‐ and enantioselectivity and without the need for a directing group.